2008
DOI: 10.1016/j.jcps.2008.09.006
|View full text |Cite
|
Sign up to set email alerts
|

Beyond fit and attitude: The effect of emotional attachment on consumer responses to brand extensions

Abstract: In two studies employing fictitious and real brands, this paper shows that brand attachment goes beyond attitude and fit in determining consumers' behavioral reactions to brand extensions such as purchase intentions, willingness to pay, word-of-mouth, and forgiveness. The effect is pronounced at high and moderate, but not low levels of fit. The paper also shows that attachment has an impact on the extent to which the extension is categorized as a member of the parent brand family, which partially mediates atta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
205
2
12

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 271 publications
(240 citation statements)
references
References 64 publications
(83 reference statements)
6
205
2
12
Order By: Relevance
“…Previous studies show that a long period of time and extensive experience of a brand is needed for brand love to develop (Holmes, 2000;Mikulincer et al, 2001), whereas brand attitude does not necessarily require such a long relationship (Fredorikhin and Thomson, 2008;Park et al, 2010), or even direct contact or personal experience with the brand. For example, Verhoef et al (2002) show that the length of brand experience positively affects several aspects of relationships, such as satisfaction, trust and commitment.…”
Section: Moderating Effects Of Brand Experience and Price Perceptionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies show that a long period of time and extensive experience of a brand is needed for brand love to develop (Holmes, 2000;Mikulincer et al, 2001), whereas brand attitude does not necessarily require such a long relationship (Fredorikhin and Thomson, 2008;Park et al, 2010), or even direct contact or personal experience with the brand. For example, Verhoef et al (2002) show that the length of brand experience positively affects several aspects of relationships, such as satisfaction, trust and commitment.…”
Section: Moderating Effects Of Brand Experience and Price Perceptionmentioning
confidence: 99%
“…Several desirable outcomes of brand love have been proposed, such as brand loyalty, positive word of mouth (WOM) (Carroll and Ahuvia, 2006;Albert and Merunka, 2013;Wallace et al, 2014), stronger purchase intentions (Fetscherin, 2014;Kudeshia et al, 2016;Pawle and Cooper, 2006), and greater willingness to pay price premiums (Albert and Merunka, 2013;Fedorikhin et al, 2008;Thomson et al, 2005) and accept product failures (Grisaffe and Nguyen, 2011). Owing to the growing influence of peer reviews and suggestions on consumers' buying decisions, positive WOM in both offline and online environments (i.e., electronic WOM [eWOM]) are the key objectives of today's marketing activities (Chen and Xie, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…brand). As an outcome of attachment, commitment is the next step in consumer-brand relationship (Fedorikhin, Park and Thomson, 2008). Even though, the serial path on commitment was found non-significant, its positive effect size can be considered as a sign of potential improvement on consumer-brand relationship.…”
Section: Resultsmentioning
confidence: 94%
“…It was revealed that this is valid especially when there is harmony between brand and the extended product. Fedorikhin, Park, & Thomson (2008) have highlighted that consumers' attitudes towards brand extensions stem from brand loyalty rather than harmony and consumers react positively to brand extensions and take purchasing There are studies that analyze consumers' approach to brand extensions in the light of cognitive paradigms (Czellar, 2003). Accordingly, there is mutual interaction between the perception of the harmony between the main brand and the extended brand by the consumer and development of their first attitudes towards extensions and their market behavior.…”
Section: Consumers' Attitudes Towards Brand Extensionsmentioning
confidence: 99%